Influence maternal background has on children's mental health - Elena Arroyo-Borrell; Gemma Renart; Carme Saurina; Marc Saez (BMC, 2017)
Abstract Background In this paper, we aim to discern how a mother's health and her socioeconomic determinants may influence her children's mental health. In addition to this, we also evaluate the influence of other household characteristics and whether or not the economic downturn has heightened the effect a parent's social gradient has on their children's mental health. Methods We use samples comprised of 4-14-year-old minors from the 2006 Spanish National Health Survey (SNHS), undertaken prior to the crisis, and the 2011 SNHS, carried out during the crisis. The participating children's mental health is assessed using the Strengths and Difficulties Questionnaire (SDQ). Mixed models are used to evaluate the influence a mother's health and her socioeconomic status may have on her children's mental health. We also add interactions to observe the effect specific socioeconomic determinants may have had during the economic downturn. Results The risk of a child suffering from mental health disorders increases when their mother has mental health problems. Socioeconomic determinants also play a role, as a low socioeconomic status (SES) increases the risk of a child exhibiting behavioural problems, being hyperactive or antisocial, whereas when a mother has attained a high level of education, this significantly reduces the probability of a child having mental health problems. 'Homemaker' is the activity status most positively related to children's mental health. The findings show that the Spanish economic downturn has not significantly changed children's mental health problems and the negative effects of low maternal SES are no greater than they were before the crisis. The main difference in 2011, with respect to 2006, is that the risk of children suffering from mental health problems is higher when their parents are (long or short-term) unemployed. Conclusions In conclusion, both a mother's health and her socioeconomic status, as well as other household characteristics, are found to be related to her children's mental well-being. Although the crisis has not significantly changed mental health disorders in children or the social gradient of parents in general, at-risk children are the most negatively affected in the Spanish economic downturn.